Quality of Life and Concerns in Parent Caregivers of Adult Children Diagnosed with Intellectual Disability: A Qualitative Study - Fernández-Ávalos, María Inmaculada (Int J Environ Res Public Health, 2020)
Background: Previous studies have confirmed that parenting a child diagnosed with an intellectual disability (ID) can negatively affect the parents’ quality of life in several dimensions. However, fewer have assessed its impact years after the initial diagnosis. The objective of this work was to carry out an in-depth analysis of the current quality of life and concerns of both mothers and fathers of adults diagnosed with ID, having as a reference the moment of the diagnosis. Methods: 16 parents of adult children with ID were evaluated using a semi-structured interview format. A thematic qualitative analysis was carried out by employing ATLAS.ti software. Results: The results suggested that both the emotional and physical well-being of parents, as well as their interpersonal relationships, had declined. In addition, the multiple life changes that had occurred over the time considered in this study, as well as day-to-day worries, had prevented improvements in their quality of life. Conclusions: Several dimensions of the parents’ quality of life were affected years after a child is diagnosed with ID. These included poor physical and psychological health, economic difficulties, lack of social and family support, and lack of time for self-care.